The Effect of Video Modeling Example, Worked-Example, and Practice Problem on Mathematics Learning - Santosa, Cecep Anwar Hadi Firdos; Novaliyosi, Novaliyosi; Putri, Zakiya Amalia Hartanto (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
Low learning results, learning motivation, and student confidence are frequently encountered when teaching mathematics in junior high school. To address these issues, it is vital to use learning methods that are appropriate for the student's qualities. The purpose of this study is to investigate and compare the impact of different learning strategies, such as video modelling examples, worked-examples, and practice problems, on students' self-efficacy, motivation, and learning outcomes in the cognitive parts of mathematics teaching. This study used a quantitative methodology and a quasi-experimental design. The study involved eighth-grade pupils from a junior high school in Serang City, who were divided into three classes and given different learning techniques. A learning outcomes exam, a self-efficacy questionnaire, and a motivation survey were used to collect data. To identify significant differences between groups, the obtained data were evaluated using a t-test, one-way ANOVA, and a post hoc Tukey HSD test. The study found that the three strategies had a substantial impact on self-efficacy, motivation, and learning results in the cognitive domain. The practice problem method is more effective at boosting self-efficacy, the video modelling example at raising learning motivation, and the worked example at enhancing learning results in cognitive areas. These findings emphasize the necessity of selecting instructional approaches that are consistent with the targeted learning objectives. Future research should look into the effectiveness of these methods across different topic areas, grade levels, or in combination with other pedagogical approaches to acquire a more complete knowledge of their effects.